COMPASS and SWI/SNF complexes in development and disease - Cenik, Bercin K; Shilatifard, Ali (Nature reviews. Genetics, 2021)
The Trithorax group (TrxG) of proteins is a large family of epigenetic regulators that form multiprotein complexes to counteract repressive developmental gene expression programmes established by the Polycomb group of proteins and to promote and maintain an active state of gene expression. Recent studies are providing new insights into how two crucial families of the TrxG - the COMPASS family of histone H3 lysine 4 methyltransferases and the SWI/SNF family of chromatin remodelling complexes - regulate gene expression and developmental programmes, and how misregulation of their activities through genetic abnormalities leads to pathologies such as developmental disorders and malignancies.